The attributable risk of chronic obstructive pulmonary disease due to ambient fine particulate pollution among older adults. (April 2018) - Lin, Hualiang; Qian, Zhengmin (Min); Guo, Yanfei; Zheng, Yang; Ai, Siqi; Hang, Jian; Wang, Xiaojie; Zhang, Lingli; Liu, Tao; Guan, Weijie; Li, Xing; Xiao, Jianpeng; et al.
Abstract: Background: The linkage between ambient fine particle pollution (PM2.5 ) and chronic obstructive pulmonary disease (COPD) and the attributable risk remained largely unknown. This study determined the cross-sectional association between ambient PM2.5 and prevalence of COPD among adults ≥50 years of age. Methods: We surveyed 29, 290 participants aged 50 years and above in this study. The annual average concentrations of PM2.5 derived from satellite data were used as the exposure indicator. A mixed effect model was applied to determine the associations and the burden of COPD attributable to PM2.5. Results: Among the participants, 1872 (6.39%) were classified as COPD cases. Our analysis observed a threshold concentration of 30 μg/m 3 in the PM2.5 -COPD association, above which we found a linear positive exposure-response association between ambient PM2.5 and COPD. The odds ratio (OR) for each 10 μg/m 3 increase in ambient PM2.5 was 1.21(95% CI: 1.13, 1.30). Stratified analyses suggested that males, older subjects (65 years and older) and those with lower education attainment might be the vulnerable subpopulations. We further estimated that about 13.79% (95% CI: 7.82%, 21.62%) of the COPD cases could be attributable to PM2.5 levels higher than 30 μg/m 3 in the study population. Conclusion: Our analysis indicates that ambient PM2.5 exposure could increase the risk of COPD and accounts for a substantial fraction of COPD among the study population. Highlights: We examined the effects of PM2.5 on COPD in adults. Annual PM2.5 was estimated using satellite data. PM2.5 was found to be associated with risk of COPD. 14% of COPD cases could be attributable to ambient PM2.5.